Comparing face-to-face and asynchronous online communication as mechanisms for critical reflective dialogue. Issue 5 (20th October 2017) - Salter, Susan; Douglas, Tracy; Kember, David
Abstract: Two mechanisms for engaging in critical reflective dialogue are discussed and compared: face-to-face meetings and asynchronous online discussion. The context is an umbrella action research project, with over 20 participants, which aimed to improve practices in online teaching and contribute to the development of graduate attributes. The article compares discussion using the two modes (face-to-face and online) of the nature of and development of problem-solving and other graduate attributes. Face-to-face discussion was wide ranging and quite loosely structured, so divergent aspects of a topic were uncovered. The asynchronous nature of online discussion, however, permitted topics to be explored more thoroughly. The two modes worked well in conjunction with one another, if aspects of face-to-face discussion topics were posted online as discussion threads. The asynchronous online discussions then allowed each thread to be explored in depth, so that collective understanding of a given topic could be enhanced.